Das Präsens im Tigre - Voigt, Rainer (Aethiopica, 2009)
In the grammatical descriptions of Tigre it is usual to quote the 3rd masc. sg. and pl. and the 3rd fem. pl. with word-initial lǝ- (e.g. 3rd masc. sg. lǝqannǝṣ ‘he gets up’, Raz 1983) where it is generally remarked upon that there is an “optional use of prefixes in the imperfect”. In the light of older grammars and especially based on recent relevant analyses of modern Tigre texts, it is qannǝṣ which should be considered as the normal form, unless the conjunction ʾǝt precedes. The elision of elements other than lǝ- is rarely documented. Verbs with laryngeals show some peculiarities.